The mistletoe mystery : a maid novella [large type] - Prose, Nita (Random House Large Print, 2024)
Molly Gray has always loved the holidays. When Molly was a child, her gran went to great lengths to make the season merry and bright, full of cherished traditions. The first few Christmases without Gran were hard on Molly, but this year, her beloved boyfriend and fellow festive spirit, Juan Manuel, is intent on making the season Molly's mofinst joyful yet. But when a Secret Santa gift exchange at the Regency Grand Hotel raises questions about who Molly can and cannot trust, she dives headfirst into solving her most consequential--and personal--mystery yet. Molly has a bad feeling about things, and she starts to wonder: has she yet again mistaken a frog for a prince?--